Direct In Situ Growth of Centimeter‐Scale Multi‐Heterojunction MoS2/WS2/WSe2 Thin‐Film Catalyst for Photo‐Electrochemical Hydrogen Evolution. Issue 13 (26th April 2019) - Seo, Sehun; Kim, Seungkyu; Choi, Hojoong; Lee, Jongmin; Yoon, Hongji; Piao, Guangxia; Park, Jun‐Cheol; Jung, Yoonsung; Song, Jaesun; Jeong, Sang Yun; Park, Hyunwoong; Lee, Sanghan
Abstract: To date, the in situ fabrication of the large‐scale van der Waals multi‐heterojunction transition metal dichalcogenides (multi‐TMDs) is significantly challenging using conventional deposition methods. In this study, vertically stacked centimeter‐scale multi‐TMD (MoS2 /WS2 /WSe2 and MoS2 /WSe2 ) thin films are successfully fabricated via sequential pulsed laser deposition (PLD), which is an in situ growth process. The fabricated MoS2 /WS2 /WSe2 thin film on p‐type silicon (p‐Si) substrate is designed to form multistaggered gaps (type‐II band structure) with p‐Si, and this film exhibits excellent spatial and thickness uniformity, which is verified by Raman spectroscopy. Among various application fields, MoS2 /WS2 /WSe2 is applied to the thin‐film catalyst of a p‐Si photocathode, to effectively transfer the photogenerated electrons from p‐Si to the electrolyte in the photo‐electrochemical (PEC) hydrogen evolution. From a comparison between the PEC performances of the homostructure TMDs (homo‐TMDs)/p‐Si and multi‐TMDs/p‐Si, it is demonstrated that the multistaggered gap of multi‐TMDs/p‐Si improves the PEC performance significantly more than the homo‐TMDs/p‐Si and bare p‐Si by effective charge transfer. The new in situ growth process for the fabrication of multi‐TMD thin films offers a novel and innovative method for the application of multi‐TMD thin films to various fields. Abstract : A multihetero MoS2 /WS2 /WSe2 thin film with a multistaggered gap is directly fabricated on p‐Si by an in situ growth process using sequential pulsed laser deposition. The built‐in electric field generated by the multistaggered gap facilitates the effective transfer of the photogenerated electrons to the electrolyte in photo‐electrochemical hydrogen evolution.